Opuntia dillenii (Ker Gawl.) Haw., Seeds Oil Antidiabetic Potential Using In Vivo, In Vitro, In Situ, and Ex Vivo Approaches to Reveal Its Underlying Mechanism of Action - Mohamed Bouhrim; Hayat Ouassou; Salima Boutahiri; Nour Elhouda Daoudi; Hamza Mechchate; Bernard Gressier; Bruno Eto; Hamada Imtara; Amal A. Alotaibi; Mohammed Al-zharani; Abderrahim Ziyyat; Hassane Mekhfi; et al. (Molecules, 2021)
Opuntia dillenii Ker Gawl. is one of the medicinal plants used for the prevention and treatment of diabetes mellitus (DM) in Morocco. This study aims to investigate the antihyperglycemic effect of Opuntia dillenii seed oil (ODSO), its mechanism of action, and any hypoglycemic risk and toxic effects. The antihyperglycemic effect was assessed using the OGTT test in normal and streptozotocin (STZ)-diabetic rats. The mechanisms of action were explored by studying the effect of ODSO on the intestinal absorption of d-glucose using the intestinal in situ single-pass perfusion technique. An Ussing chamber was used to explore the effects of ODSO on intestinal sodium-glucose cotransporter 1 (SGLT1). Additionally, ODSO’s effect on carbohydrate degrading enzymes, pancreatic α-amylase, and intestinal α-glucosidase was evaluated in vitro and in vivo using STZ-diabetic rats. The acute toxicity test on mice was performed, along with a single-dose hypoglycemic effect test. The results showed that ODSO significantly attenuated the postprandial hyperglycemia in normal and STZ-diabetic rats. Indeed, ODSO significantly decreased the intestinal d-glucose absorption in situ. The ex vivo test (Ussing chamber) showed that the ODSO significantly blocks the SGLT1 (IC50 = 60.24 µg/mL). Moreover, ODSO indu\ced a significant inhibition of intestinal α-glucosidase (IC50 = 278 ± 0.01 µg/mL) and pancreatic α-amylase (IC50 = 0.81 ± 0.09 mg/mL) in vitro. A significant decrease of postprandial hyperglycemia was observed in sucrose/starch-loaded normal and STZ-diabetic ODSO-treated rats. On the other hand, ODSO had no risk of hypoglycemia on the basal glucose levels in normal rats. Therefore, no toxic effect was observed in ODSO-treated mice up to 7 mL/kg. The results of this study suggest that ODSO could be suitable as an antidiabetic functional food.